2019
DOI: 10.18632/oncotarget.26859
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cancer risk after kidney transplantation

Abstract: Kidney transplant (KT) recipients are at greater risk of developing some cancers than the general population. Moreover, cancer is the only cause of death that is currently increasing after kidney transplantation. We analyzed incidence, risk factors and characteristics of post-transplant malignancies (solid organ tumors and lymphoproliferative disorders) at our center in 925 KT recipients (1979-2014). Sex differences were particularly assessed. One hundred and eight patients (11.7%) developed solid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 69 publications
3
7
1
Order By: Relevance
“…Tobacco is the main risk factor, also after KT. Earlier investigations found an increased risk for lung cancer after KT, especially in females, that was not seen in the present study (Table 2) [10].…”
Section: Specific Cancers and Their Epidemiological Analysescontrasting
confidence: 81%
See 1 more Smart Citation
“…Tobacco is the main risk factor, also after KT. Earlier investigations found an increased risk for lung cancer after KT, especially in females, that was not seen in the present study (Table 2) [10].…”
Section: Specific Cancers and Their Epidemiological Analysescontrasting
confidence: 81%
“…The risk varies for all malignancies and is believed to be multifactorial but possibly triggered by the chronic exposure to immunosuppressive agents [6][7][8]. With the improving long-term outcome after transplantation, de-novo malignancies have become one of the three major causes of death after transplantation while death from cardiovascular disease and infections are decreasing in frequency [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary Table S3 provides details of the included studies, which involved e1848068-2 a total of 2,105,122 solid organ transplant recipients and reported 45 types of site-specific cancer. Of them, 52 studies 7,8,75 provided SIRs of multiple cancers of solid organ transplantations (11 for multiple organs, 7,8,[17][18][19][20][21][22][23][24][25] 19 for kidney, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] 16 for liver, [45][46][47][48][49][50][51][52][53][54][55]75 7 for heart and/or lung [60][61][62][76]…”
Section: Systematic Search and Study Characteristicsmentioning
confidence: 99%
“…To those who suffer from AUFI, UTx endows them the legal, biological and gestational motherhood and helps to give them the possibility to experience both the physical and the emotional aspects of pregnancy. However, transplant recipients of solid organs have been documented to be at a higher risk of developing diabetes mellitus and malignancies, especially for female patients . But it is interesting that stratification based on geographical region indicated that the pooled standardized incidence rates of cancers in Asian populations of renal transplant recipients (RTR) were lower than those in non‐Asian RTR .…”
Section: Long Term Health Issues Of the Recipients And Offspringmentioning
confidence: 99%
“…However, transplant recipients of solid organs have been documented to be at a higher risk of developing diabetes mellitus and malignancies, especially for female patients. [43][44][45][46] But it is interesting that stratification based on geographical region indicated that the pooled standardized incidence rates of cancers in Asian populations of renal transplant recipients (RTR) were lower than those in non-Asian RTR. 47 What is more, unlike the kidney, liver and other solid organs, the transplanted uterus can be removed after 1-2 live deliveries.…”
Section: Long Term Health Issues Of the Recipients And Offspringmentioning
confidence: 99%